The Influence of Clinical Leadership on Nurses’ Cultural Competence in Reducing Patient Anxiety in the Inpatient Ward of Nurul Hasanah Hospital - Yusnaini, Yusnaini; Arif Irpan Tanjung; Nandara Priyanti Elna (Jurnal EduHealth, 2024)
Healthcare services in Indonesia, as a multicultural country, face challenges in providing culturally sensitive nursing care. Clinical leadership plays a crucial role in developing nurses’ cultural competence to reduce patient anxiety, which can influence the healing process. This study aimed to examine the influence of clinical leadership on nurses’ cultural competence and its role in reducing patient anxiety in the inpatient ward of Nurul Hasanah Hospital. This study employed a quantitative cross-sectional design, involving 120 nurses and 150 patients selected through purposive sampling. Data were collected using the Clinical Leadership Survey, Intercultural Competence Scale in Nursing, and State-Trait Anxiety Inventory (STAI). Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results showed that clinical leadership was rated high (mean = 3.82), cultural competence moderate (mean = 3.45), and patient anxiety moderate (mean = 42.8). Clinical leadership had a positive effect on cultural competence (β = 0.687, p < 0.001) and a negative effect on patient anxiety (β = -0.214, p = 0.004). Cultural competence negatively affected patient anxiety (β = -0.478, p < 0.001) and partially mediated the relationship between clinical leadership and patient anxiety (β = -0.328, p < 0.001). Clinical leadership effectively reduces patient anxiety both directly and indirectly by enhancing nurses’ cultural competence. Strengthening clinical leadership and cultural competence may contribute to more culturally responsive and psychologically safe inpatient care.